2014
DOI: 10.4111/kju.2014.55.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of High-Risk Human Papillomavirus Infection in Male Genital Warts

Abstract: PurposeTo evaluate the prevalence and type distribution of high-risk human papillomavirus (HPV) infection in genital warts of Korean men, and for the first time, to describe the risk factors associated with high-risk HPV infection in male genital warts.Materials and MethodsIn a single private clinic, 150 consecutive male patients with histopathologic-confirmed genital warts who underwent HPV genotyping by use of polymerase chain reaction (PCR) were included in this study. We detected HPV DNA in male genital wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 30 publications
4
17
0
6
Order By: Relevance
“…HPV type 16 was shown to be the second most common type of HR types in both the total genital condyloma and non-urethral condyloma groups. Conversely, in the urethral condyloma group, HPV type 16 (12.5%) was the most frequently detected, and this result is consistent with previous reports [15][16][17][18][19]. Arroyo et al [9] reported that HPV type 16 was related to a higher number of lifetime sexual partners; the subjects in each previous study had differences of sexual partners and sexual behavior, thus influencing the prevalence of HPV types, including HPV type 16.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…HPV type 16 was shown to be the second most common type of HR types in both the total genital condyloma and non-urethral condyloma groups. Conversely, in the urethral condyloma group, HPV type 16 (12.5%) was the most frequently detected, and this result is consistent with previous reports [15][16][17][18][19]. Arroyo et al [9] reported that HPV type 16 was related to a higher number of lifetime sexual partners; the subjects in each previous study had differences of sexual partners and sexual behavior, thus influencing the prevalence of HPV types, including HPV type 16.…”
Section: Discussionsupporting
confidence: 81%
“…This finding was inconsistent with the previous studies. In addition, samples in which HPV type 6 or 11 were detected accounted for 53.6% to 91.7% in previous studies [8,15,16]. In our study, all samples from the urethral condyloma group and 90.2% from the non-urethral condyloma group had HPV type 6 or 11.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…В меньшей степени известно о течении ПВИ такого рода у мужчин, при том, что распространенность ВПЧ в мужской попу-ляции, согласно зарубежным данным [3], колеблет-ся от 5,5 до 76%. Для мужчин не существует стан-дартных программ, направленных на выявление носителей вируса при латентной и субклинической формах, наиболее надежным диагностическим ме-тодом при отсутствии клинических проявлений яв-ляется тестирование на ДНК ВПЧ [4,5].…”
unclassified
“…Как известно, инфекция, обусловлен-ная ВПЧ, у мужчин протекает преимущественно в субклинической форме. Это приводит к потенциаль-но большому числу бессимптомных носителей, кото-рые служат резервуаром и переносчиком вируса [3,4,6]. В результате обнаружение ВПЧ онкогенных типов становится проблемой не только инфицированных пациентов, но начинает представлять угрозу и для их сексуальных партнеров [4,9,10].…”
unclassified